The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-04062-5
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting water quality parameters using artificial neural network for irrigation purposes

Abstract: This study was aimed at analyzing the water quality of Ele River Nnewi, Anambra State for irrigation purposes with a view to predicting a one-year water quality index using Artificial Neural Network (ANN). Water pollution has posed a major problem and identifying the points of pollution in the River system is a very difficult task. To overcome this task, the need to determine the pollution level arose by modeling and predicting four water quality parameters at four (4) different locations using the Artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…An artificial neural network, which works similar to the human nervous system 13 , 14 , consists of an input layer of neurons (or nodes, units), one or two or even three hidden layers of neurons, and a final layer of output neurons 15 17 . ANNs have self-learning capabilities that enable them to produce better results as more data becomes available.…”
Section: Introductionmentioning
confidence: 99%
“…An artificial neural network, which works similar to the human nervous system 13 , 14 , consists of an input layer of neurons (or nodes, units), one or two or even three hidden layers of neurons, and a final layer of output neurons 15 17 . ANNs have self-learning capabilities that enable them to produce better results as more data becomes available.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical parameters of ground water play an important role in the classification and evaluation of water quality. It is noted that the best results can only be obtained when studying the ion complex in water, and not the concentration of individual ions [9]. Chemical classification also shows the concentration of various dominant cations, anions and their relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Various analytical models are used to predict water quality, which can be divided into traditional, based on statistical models, and non-traditional, using artificial intelligence (AI) approaches. Methods of KNN, machine learning, artificial neural networks (ANN) can be attributed to non-traditional methods, and regression analysis, time series methods can be attributed to traditional methods [9]. A review of the literature has shown that artificial neural networks (ANN) are at the peak of popularity in modeling the prediction of water pollution [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…We select the activation function and learning rate by referring to the neural network structure commonly used in similar fields (1 hidden layer and 64 hidden nodes) 29 , 30 . It is found that ReLU has better performance than other activation functions (sigmoid, tanh).…”
Section: Methodsmentioning
confidence: 99%